The conceptualization and Symbolization of the “Ball” and the “baton” in mystical Poetical Texts - mehdi ramazani; n a (مطالعات زبانی و بلاغی, 2016)
Poetry is a Kind of performance at the hands of words, more exact choose of words ,the more successful the poet is in transferring his experiences. Additionally, there are words in language and culture, which enter to a poet’s associative mind through harmony and juxtaposition, moreover, they cause harmony and meaningful music through ambiguity,… . Amongst these words are poetic couplets. These include: “sigh” and “mirror”, “stone” and “vase”, “particle” and “Sunshine”, “Khosro” and “shirin”, “day” and ”night” ,…. These have been tied together with invisible threads in lower layers, more artistically and skillfully. Amongst these poetical couplets are the ball and the baton. Using the relationship between harmony and juxtaposition, jementics and their various application, various couplets have been created. The frequency of these poetical couplets are so great that it causes every enthusiast to ask this question: how have poets and mystics made use of a game which has got nothing to do with mystical debates? The present article is an attempt to re –read mystical texts which shed light on the various aspects/ applications of the ball and the baton. It concludes that poets and mystics have conceptualised and symbolised this poetical couplet in various cases especially when dealing with the various states of the lover and the beloved.   Keywords: